Can't Let It Go: Hate in Interpersonal Relationships. (29th February 2016) - Aumer, Katherine; Bahn, Anne Cathrine Krebs; Janicki, Cortney; Guzman, Nicolas; Pierson, Natalie; Strand, Susanne Estelle; Totlund, Helene
Abstract : Theories concerning hatred in personal relationships lack empirical evidence. These two studies address the need to provide empirical information about how hate works in interpersonal, loving relationships. Effort justification theory (Aronson & Mills, 1959 ) suggests that past hate may have a beneficial function in relationships that remain together; however, if hate is a truly destructive motivation (Rempel & Burris, 2005 ), this hate may have a lasting irreconcilable impact on the quality of the relationship. By surveying people in both the United States and Norway about their personal loving relationships, we discovered that hatred leaves a lasting deleterious impression on interpersonal relationships. People are more likely to report less intimacy, satisfaction, and love with people they have previously hated. Furthermore, effort justification and cognitive dissonance, when measured as relationship length, was observed in the report of higher commitment to those previously hated. Future assessments of relationship quality should consider measuring hatred and length of relationship.